The Palgrave handbook of disability sport in Europe. Policies, structures and participation (Palgrave Macmillan, 2023)
This handbook explores the various ways in which disability sport is governed and organised across Europe, as well as examining the extent to which persons with a disability participate in sport at the grassroots level. Based upon a solid theoretical framework and up-to-date data, the 19 country-specific chapters in this handbook give a comparative overview of the structuring, steering and supporting elements of disability sport policy and sport participation levels amongst persons with a disability, as well as the extent to which countries adopt policies to promote inclusion in sport in this population. A multitude of authors also identify the various methods and challenges in collecting sport participation data with regard to persons with a disability. This handbook will be a valuable resource for academic study across a range of sport and disability related programs, as well as a point of reference for researchers and policymakers working in this area.